Before you say anything : the untold stories and failproof strategies of a very discreet speechwriter - Wellman, Victoria (Speechwriter) (St. Martin's Press, 2022)
"Victoria Wellman's Before You Say Anything invites readers into the game-changing creative process of New York's busiest speechwriter, delivering actionable insights for anyone tasked with speaking in public. In the age of information and influence, the ability to authentically express yourself in words has become both a rite of passage and an essential skill for anyone who wants to make a difference-however modest or grand-in their family, community, workplace, or at the podium in front of thousands. And yet the conventional wisdom around what resonates for today's speakers and their audiences has failed to evolve, leaving speakers wondering how they will craft a speech that provides the individuality, originality and authenticity our culture demands. While we can't all be the next Amanda Gorman, however, there is a roadmap every speaker can follow-regardless of their experience-to elevate a narrative from serviceable to unforgettable. This is true whether you are roasting a colleague at an office party, delivering a keynote industry address, accepting an award, or eulogizing a loved one. In Before You Say Anything, Victoria Wellman-the founder and president of Manhattan-based speechwriting company The Oratory Laboratory-shares her unique methodology for researching, reimagining, crafting, and delivering a professional quality speech by focusing on three core objectives: respect for the audience, the restless pursuit of originality, and intentionality behind every word. Full of hilarious anecdotes and examples from Wellman's extensive experience as the go-to speechwriter for power players and everyday people from around the world, Before You Say Anything is an irresistible antidote to the age-old doctrine of what a speech must include. Instead it will leave readers with an enlightened and refreshing way of thinking about their sources, ideas and material, and a strategy of putting it all to use"--